2023
DOI: 10.21203/rs.3.rs-3582420/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aesthetic Chills Mitigate Maladaptive Cognition In Depression

Felix Schoeller,
Abhinandan Jain,
Vladimir Adrien
et al.

Abstract: Background Depression is a major global health challenge, affecting over 300 million people worldwide. Current pharmacological and psychotherapeutic interventions have limited efficacy, underscoring the need for novel approaches. Emerging evidence suggests that peak emotional experiences characterized by awe, transcendence, and meaning hold promise for rapidly shifting maladaptive cognitive patterns in depression. Aesthetic chills, a peak positive emotion characterized by physical sensations such as shivers a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 33 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…The findings revealed that chills positively alter (depressogenic) negative self-schemas (e.g., related to shame and self-acceptance) (Schoeller et al, 2023c). Crucially, the phenomenology associated to the belief change induced by CS closely resemble the effects observed in psychedelic-assisted therapy, including the characteristic associated phenomenology of emotional breakthrough (EBI, Roseman et al, 2019) (Schoeller et al, 2023c), psychological insight (PIS, Peil et al, 2022) (Schoeller et al, 2023d), and ego dissolution (Nour et al, 2016) (Christov-Moore et al, 2023 (Figure 4). The surprising, involuntary nature of chills, their emergence without conscious learning, and their underlying neurobiology suggest a strong similarity to so-called primary states of consciousness (Schoeller et al, 2023c), which are considered phylogenetically older states of consciousness often associated with profound changes in beliefs, perceptions, and behavior (Schoeller, 2023;Carhart-Harris et al, 2014).…”
Section: Dopamine and Precision Encoding In Aesthetic Chillsmentioning
confidence: 82%
See 4 more Smart Citations
“…The findings revealed that chills positively alter (depressogenic) negative self-schemas (e.g., related to shame and self-acceptance) (Schoeller et al, 2023c). Crucially, the phenomenology associated to the belief change induced by CS closely resemble the effects observed in psychedelic-assisted therapy, including the characteristic associated phenomenology of emotional breakthrough (EBI, Roseman et al, 2019) (Schoeller et al, 2023c), psychological insight (PIS, Peil et al, 2022) (Schoeller et al, 2023d), and ego dissolution (Nour et al, 2016) (Christov-Moore et al, 2023 (Figure 4). The surprising, involuntary nature of chills, their emergence without conscious learning, and their underlying neurobiology suggest a strong similarity to so-called primary states of consciousness (Schoeller et al, 2023c), which are considered phylogenetically older states of consciousness often associated with profound changes in beliefs, perceptions, and behavior (Schoeller, 2023;Carhart-Harris et al, 2014).…”
Section: Dopamine and Precision Encoding In Aesthetic Chillsmentioning
confidence: 82%
“…Hence, identifying the relationship between aesthetic chills, the precision-weighting of prediction errors, and its dopaminergic substrate could help to understand the role of dopamine in these conditions. Using a recently constituted database of CS, some preliminary studies have investigated the effects of aesthetic chills on subjects diagnosed with Major Depressive Disorder (Jain et al, 2023a;Schoeller et al, 2023c). Preliminary data suggest that chills have an effect in mood disorders (Jain et al, 2023a: Jain et al, 2023bSchoeller et al, 2023c).…”
Section: Dopamine and Precision Encoding In Aesthetic Chillsmentioning
confidence: 99%
See 3 more Smart Citations